Digital Impact on Indian Society - Dr. Vinod Kumar (Journal of Linguistics and Communication Studies, 2024)
The Digital India Mission, launched in 2015, is a visionary initiative by the Government of India to transform the country into a digitally empowered society and knowledge economy. This ambitious Digital India Program aims to bridge the digital divide, connect rural and urban populations, and enable access to essential government services, education, healthcare, and financial inclusion through the power of technology. The Digital India Mission is a flagship initiative to harness the power of digital technology to transform the country into a digitally empowered society and knowledge economy. In an era marked by rapid technological advancements and the widespread integration of digital platforms into various aspects of our lives, the term “Digital India” resonates as more than just a catchphrase. It embodies a vision of transformative change, where technology acts as a catalyst for growth, inclusivity, and progress on an unprecedented scale. Hence, an attempt has been made in this paper to understand Digital India — as a campaign where technologies and connectivity will come together to make an impact on all aspects of governance and improve the quality of life of citizens.